Fosfomycin susceptibility among multidrug-resistant, extended-spectrum beta-lactamase-producing, carbapenem-resistant uropathogens - Banerjee, Sayantan (Indian J Urol, 2017)
INTRODUCTION: Urinary tract infection (UTI) is one of the most common infectious diseases. With the emergence of multidrug resistance (MDR), therapeutic options for treatment of UTIs are becoming limited. Fosfomycin has emerged as a novel oral therapeutic option with bactericidal activity against the MDR uropathogens. We evaluated the susceptibility pattern of uropathogens to this antibiotic. METHODS: A prospective study was conducted for 6 months in a tertiary care hospital in Eastern India to evaluate whether the common uropathogens were susceptible to fosfomycin. Identification of organisms causing significant bacteriuria was done by conventional biochemical and VITEK 2 Compact System™. Antimicrobial susceptibility testing was performed against these pathogens by Kirby-Bauer disc diffusion method. Minimum inhibitory concentrations were measured for certain drugs by E-strips and VITEK 2 Compact System. RESULTS: A total of 2229 urine samples were referred for culture during the study period, which yielded 356 significant bacterial isolates. Among these isolates, 64.78% were extended-spectrum beta-lactamases producers, 15.97% were carbapenem-resistant Enterobacteriaceae, and 42.7% isolates were found to be MDR Enterobacteriaceae (MDRE). However, 95.18% of the total isolates and 95.93% of MDRE were found to be susceptible to fosfomycin. CONCLUSION: The common uropathogens, including MDR isolates, show high in vitro susceptibility to fosfomycin, which therefore has the potential to emerge as a promising alternative oral agent for outpatient therapy of UTIs.